DEVELOPMENT OF GASTRODUODENAL PATHOLOGY IN CHILDREN WITH REGULAR USE OF HIGHLY MINERALIZED WATER - Sadikova Raykhon Rakhimbekovna (Bright Mind Publishing, 2025)
The increasing consumption of highly mineralized drinking water among children has attracted clinical and public health attention due to the potential impact on the gastrointestinal system. This article examines the clinical-prognostic significance of gastroduodenal pathology in children associated with chronic intake of high-mineral content water. Based on literature sources and synthesized findings, the study explores how elevated concentrations of sodium, sulfates, chlorides, calcium, and magnesium influence gastric and duodenal mucosa, alter acid-base homeostasis, and contribute to dyspeptic disorders, inflammation, and erosion-ulcerative lesions in pediatric patients. The article also identifies key risk factors, clinical manifestations, prognostic complications, and preventive strategies aimed at minimizing adverse outcomes.
Keywords: Gastroduodenal pathology, children, mineralized water, gastrointestinal disorders, gastric mucosa, duodenitis, gastritis, mineral composition, prognosis, pediatric gastroenterology.